Targeted modification of the Per2 clock gene alters circadian function in mPer2luciferase (mPer2Luc) mice - Ralph, Martin R; Shi, Shu-Qun; Johnson, Carl H; Houdek, Pavel; Shrestha, Tenjin C; Crosby, Priya; O'Neill, John S; Sládek, Martin; Stinchcombe, Adam R; Sumová, Alena (PLoS computational biology, 2021)
Modification of the Per2 clock gene in mPer2Luc reporter mice significantly alters circadian function. Behavioral period in constant dark is lengthened, and dissociates into two distinct components in constant light. Rhythms exhibit increased bimodality, enhanced phase resetting to light pulses, and altered entrainment to scheduled feeding. Mechanistic mathematical modelling predicts that enhanced protein interactions with the modified mPER2 C-terminus, combined with differential clock regulation among SCN subregions, can account for effects on circadian behavior via increased Per2 transcript and protein stability. PER2::LUC produces greater suppression of CLOCK:BMAL1 E-box activity than PER2. mPer2Luc carries a 72 bp deletion in exon 23 of Per2, and retains a neomycin resistance cassette that affects rhythm amplitude but not period. The results show that mPer2Luc acts as a circadian clock mutation illustrating a need for detailed assessment of potential impacts of c-terminal tags in genetically modified animal models.
Keywords: Circadian Rhythm; Behavior, Animal; cirkadiánní proteiny Period; cirkadiánní rytmus; myši inbrední C57BL; mutace; Mice; stravovací zvyklosti; Luciferases; luciferasy; Locomotion; Mutation; zvířata; chování zvířat; myši; Feeding Behavior; Period Circadian Proteins; lokomoce; Mice, Inbred C57BL; Animals